Establishing the reliability of test procedures in order to investigate the effect of penetrating trunk trauma and prolonged mechanical ventilation on the recovery of adult survivors - H. van Aswegen; C. J. Eales; G. A. Richards (AOSIS, 2007)
Gunshot wounds and/or stab wounds to the trunk are injuries commonly seen in South African hospitals. Such injuries often necessitate exploratory surgical intervention to identify and treat injuries to the internal organs. These patients are managed in the intensive care unit and often undergo prolonged mechanical ventilation with immobilization that often results in some degree of muscle dysfunction. In order to monitor the recovery of adult survivors over a 6-month period after hospital discharge, validation of the six-minute walk test and hand-held dynamometry between data collectors was necessary. Methods: Data was collected for the six-minute walk test and hand-held dynamometry by three data collectors.  Subsequently a correlation coefficient (Pearson product moment correlate) was calculated and one-way analysis of variance (ANOVA) performed to assess the degree of association between the data. Results and Discussion: A strong positive correlation existed for data collected on the 6-minute walk test between data collectors 1, 2 and 3 with r ranging from 0.71 to 1  (p < 0.025 to p < 0.0005). The intra-class correlation (ICC) scores between data collectors ranged from 0.69 to 0.90 confirming this finding.  A weak to fair correlation existed between data collectors for dynamometry measurements of the triceps and quadriceps muscles. Intra-class correlation scores ranged from 0.11 to 0.71. Conclusion: A strongly positive inter-observer correlation existed for data sets for the six-minute walk test. A weak intra-observer correlation existed for data sets collected by data collectors for dynamometry however this improved with intervention. The degree of association between data sets for dynamometry should be assessed again during the main study.